Digital Visibility Institusi Pendidikan Tinggi: Analisis Praktik Komunikasi Kampus melalui Instagram Berdasarkan Data Instagram Professional Dashboard - Khusnul Amalin; Habib Ismail Ismail; M. Zulfi Ifani; Sunan Hanif Ismail; Syira Riyanisa Pratama Shinta; Nurdini Tsabitul Chusna (Prodi Sosiologi Universitas Mataram, 2026)
This study analyzes the digital visibility of higher education institutions on Instagram as a socially constructed process shaped by platform logic. Drawing on digital visibility studies, platform studies, and the sociology of communication, Instagram is conceptualized not merely as a communication medium but as a non-human actor that actively structures institutional visibility through algorithmic mechanisms and performance metrics. The study employs data from Instagram Professional Dashboard, including reach, impressions, and engagement, to examine the relationship between institutional communication practices and the technological architecture of the platform within a competitive digital public sphere. The findings indicate that digital visibility is neither neutral nor fully controllable by institutions, but emerges through ongoing negotiation between organizational strategies, algorithmic preferences, and audience responses. Audiovisual and human-centered content tends to achieve higher visibility than formal informational posts, illustrating the selective nature of visibility in the digital attention economy. Furthermore, high reach does not necessarily correspond with meaningful engagement, suggesting that visibility on social media is often temporary and superficial. From a sociological perspective, the study reveals an asymmetrical power relationship between higher education institutions and social media platforms. While Instagram enables expanded public presence, institutions become increasingly dependent on platform-driven metrics and logics of attention, placing them in a paradoxical position. This study contributes to digital visibility and institutional communication scholarship by offering a critical understanding of social media as a structured, negotiated, and power-laden media environment shaping contemporary campus communication practices.